Ensiling process and pomegranate peel extract as a natural additive in potential prevention of fungal and mycotoxin contamination in silage. (2022) - Sadhasivam, Sudharsan; Marshi, Rula; Barda, Omer; Zakin, Varda; Britzi, Malka; Gamliel, Abraham; Sionov, Edward
Abstract: A study was conducted on six animal feed centers in Israel where fungal and mycotoxin presence was examined in maize and wheat silages. Fumonisin mycotoxins FB1 and FB2 were present in every maize silage sample analyzed. Interestingly, no correlation was found between the occurrence of specific mycotoxins and the presence of the fungal species that might produce them in maize and wheat silages. We further investigated the effect of pomegranate peel extract (PPE) on Fusarium infection and fumonisin biosynthesis in laboratory-prepared maize silage. PPE had an inhibitory effect on FB1 and FB2 biosynthesis by Fusarium proliferatum, which resulted in up to 90 % reduction of fumonisin production in silage samples compared to untreated controls. This finding was supported by qRT-PCR analysis, showing downregulation of key genes involved in the fumonisin-biosynthesis pathway under PPE treatment. Our results present promising new options for the use of natural compounds that may help reduce fungal and mycotoxin contamination in agricultural foodstuff, and potentially replace traditionally used synthetic chemicals. Graphical Abstract: ga1 Highlights: The mycotoxins fumonisin B1 and B2 were detected in all analyzed maize silage samples. No correlation was found between mycotoxins and their fungal sources in silages. Treatment with PPE demonstrated strong anti-mycotoxigenic activity in silages samples.